N-(2-Chlorophenyl)-4-hydroxy-2H-1,2-benzothiazine-3-carboxamide 1,1-dioxide - Siddiqui, Waseeq Ahmad (International Union of Crystallography, 2009)
In the title compound, C(15)H(11)ClN(2)O(4)S, there are two independent molecules in the asymmetric unit, in which the heterocyclic thiazine rings in both molecules adopt half-chair conformations. The conformations about the C—C and C—N bonds in the central C—C—N—C chain in both molecules are all EZ. There are strong intramolecular O—H⋯O and N—H⋯N hydrogen bonds resulting in graph-set patterns S(6) and S(5) for the oxo and amino rings, in addition to intramolecular N—H⋯Cl interactions. In the crystal structure, molecules are linked by intermolecular O—H⋯O and N—H⋯O hydrogen bonds into chains along [100].